Factors associated with diagnosis of stages I and II lung cancer: a multivariate analysis - Isabel Cristina Martins Emmerick; Anupama Singh; Maggie Powers; Feiran Lou; Poliana Lin; Mark Maxfield; Karl Uy (Universidade de São Paulo, 2021)
ABSTRACT OBJECTIVE To present the overall survival rate for lung cancer and identify the factors associated with early diagnosis of stage I and II lung cancer. METHODS This is a retrospective cohort study including individuals diagnosed with lung cancer, from January 2009 to December 2017, according to the cancer registry at UMass Memorial Medical Center. Five-year overall survival and its associated factors were identified by Kaplan-Meier curves and Cox's proportional hazards model. Factors associated with diagnosing clinical stage I and II lung cancer were identified by bivariate and multivariate backward stepwise logistic regression (Log-likelihood ratio (LR)) at 95% confidence interval (CI). RESULTS The study was conducted with data on 2730 individuals aged 67.9 years on average, 51.5% of whom female, 92.3% white, and 6.6% never smoked. Five-year overall survival was 21%. Individuals diagnosed with early-stage disease had a 43% five-year survival rate compared to 8% for those diagnosed at late stages. Stage at diagnosis was the main factor associated with overall survival [HR = 4.08 (95%CI: 3.62-4.59)]. Factors associated with early diagnosis included patients older than 68 years [OR = 1.23 (95%CI: 1.04-1.45)], of the female gender [OR = 1.47 (95%CI: 1.24-1.73)], white [OR = 1.63 (95%CI: 1.16-2.30)], and never-smokers [OR = 1.37 (95%CI: 1.01-1.86)]; as well as tumors affecting the upper lobe [OR = 1.46 (95%CI: 1.24-1.73)]; adenocarcinoma [OR = 1.43 (95%CI: 1.21-1.69)]; and diagnosis after 2014 [OR = 1.61 (95%CI: 1.37-1.90)]. CONCLUSIONS Stage at diagnosis was the most decisive predictor for survival. Non-white and male individuals were more likely to be diagnosed at a late stage. Thus, promoting lung cancer early diagnosis by improving access to health care is vital to enhance overall survival for individuals with lung cancer.